Photoluminescent copper(I) iodide alkylpyridine thin films as sensors for volatile halogenated compounds - Jamshidi, Mahboubeh; Bouheriche, Joey; Gardner, James M. (Frontiers in Chemistry, 2023)
The paper presents the fabrication and characterization of [CuI(L)]n thin films, where L represents various alkylpyridine ligands including 4-methylpyridine, 3-methylpyridine, 2-methylpyridine, 4-tbutylpyridine, 3,4-dimethylpyridine, and 3,5-dimethylpyridine. The thin films were synthesized by exposing the corresponding ligands to CuI thin films through vapor deposition. The coordination reactions occurring on the films were investigated using PXRD and time-dependent photoluminescence spectroscopy, and a comparison was made between the structures of the thin films and the corresponding powder phases. The films showed primarly blue emission (λem = 457–515 nm) and polymeric structures with excited state lifetimes ranging from 0.6 to 5.5 μs. Significantly, the studied compounds exhibited fast reversible luminescence quenching when exposed to vapors of dichloromethane and dibromomethane (15 and 30 min respectively), and the luminescence was restored upon re-exposure to the alkylpyridine ligand (after 20 min). These findings indicate that these thin films hold promise for applications as sensors (with sensitive and reversible detection capability) for volatile halogen-based compounds (VHC).